Harnessing Electrical Power from Hybrid Biomass-Solid Waste Energy Resources for Microgrids in Underdeveloped and Developing Countries - Raza, M. A.; Khatri, K. L.; Rafique, K.; Saand, A. S. (Engineering, Technology & Applied Science Research, 2021)
This paper presents an energy plan for harnessing electrical power from hybrid energy resources, including biomass and solid waste, through hybrid technologies for microgrid development to overcome the current energy crisis and provide future sustainable electricity pathways for a developing country. Biomass and solid waste were collected from different dumping sites in Pakistan and were tested for their calorific value, which was found to be 6519Kcal/Kg. The total power was calculated based on this calorific value and it was found that there is a potential of total 11,989.5GW of power generation. Thus, hybrid energy resources are suitable for harnessing electrical energy through hybrid technologies. Different hybrid systems were examined for these resources and the gasification technique is finally proposed as the most suitable method for producing energy from biomass and solid waste resources in Pakistan. This technique is also found to be economically feasible for processing all kinds of waste.